Unmet financial obligations and alcohol-related mortality: A nationwide register-based follow-up study - Yerko Rojas (Elsevier, 2022)
This study sets out to explore whether experiencing financial indebtedness is related to alcohol-related mortality. For this purpose, people aged between 20 and 64 having a registration date for a debt in the Swedish Enforcement Authority's register during 2015 (n = 48,541) were followed up for a five-year period for alcohol-related mortality and were compared with a sample from the general Swedish population (n = 261,148). On the basis of logistic regression analysis, it is shown that people who had experienced financial indebtedness were almost two and a half times more likely to suffer from alcohol-related death than those who had not lived through this experience (OR = 2.43), controlling for several demographic, socio-economic, and health conditions prior to the date of the registration at the Enforcement Authority. The results provide support for the notion that debt repayment problems may, in itself, be an important indicator to consider in the study of alcohol-related harm. Consequently, debt counselling and other programs directed toward mitigating debt-related stress may play an important role in alleviating the adverse effects of indebtedness.